Diagnostic Ultrasound Safety Review for Point‐of‐Care Ultrasound Practitioners. (23rd December 2019) - Miller, Douglas L.; Abo, Alyssa; Abramowicz, Jacques S.; Bigelow, Timothy A.; Dalecki, Diane; Dickman, Eitan; Donlon, John; Harris, Gerald; Nomura, Jason
Abstract : Potential ultrasound exposure safety issues are reviewed, with guidance for prudent use of point‐of‐care ultrasound (POCUS). Safety assurance begins with the training of POCUS practitioners in the generation and interpretation of diagnostically valid and clinically relevant images. Sonographers themselves should minimize patient exposure in accordance with the as‐low‐as‐reasonably‐achievable principle, particularly for the safety of the eye, lung, and fetus. This practice entails the reduction of output indices or the exposure duration, consistent with the acquisition of diagnostically definitive images. Informed adoption of POCUS worldwide promises a reduction of ionizing radiation risks, enhanced cost‐effectiveness, and prompt diagnoses for optimal patient care.